Online Learning during Corona Virus 2019: Empirical Analysis - Bhatti, Muhammad Tariq (Richtmann Publishing, 2021)
Corona Virus Disease (COVID-19) was declared a worldwide pandemic by the World Health Organization (WHO) on mid of March 2020. Globally, most governments - including Pakistan - approved extraordinary social control measures to stem the tide of this pandemic disease. These actions required social segregation and a temporary suspension of education. As with all other institutions of higher education, public and private universities will also be required to offer distance learning to students by the end of the academic year 2020–2021. Universities of private and public sector, at all levels of higher education, suspended physical classes and implemented online teaching for university students. And, this spontaneous, quick, and uncertain nature of the teaching created difficulties for students. Data on accepted procedures for directing such sudden transitions to university education were scarce, and there was no consensus on the best way to proceed. Students at public and private universities have been impacted by a shift to distance education. Studying students' academic difficulties and the unexpected benefits of distance education, and then using that information to develop strategies that could be used in emergency situations in university education, was the goal of the study. Received: 3 August 2021 / Accepted: 7 October 2021 / Published: 5 November 2021